The Effect of Entrepreneurship Orientation and Social Capital on Entrepreneur Success in Food MSMEs in West Sumatera, Indonesia - Primadona Primadona; Emrizal Emrizal (Budapest International Research and Critics University, 2022)
Research on entrepreneurial orientation towards business performance has become a broad finding in various business fields. This study shows the effect of entrepreneurial orientation and social capital on entrepreneurial success. The research was conducted on MSMEs with the object of research being MSME owners with a sample of 600 food MSME owners in West Sumatra. The research was conducted using a quantitative method using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) application. The research location is West Sumatra, Indonesia. The results of the study reveal that entrepreneurial orientation directly and positively related to entrepreneurial success, entrepreneurial orientation also positively and significantly related to social capital, and social capital has a positive and significant effect on entrepreneurial success. Social capital as a mediating variable has a partial role in the relationship between entrepreneurial orientation and entrepreneurial success. Social capital as a mediating variable strengthens the relationship between entrepreneurial orientation and entrepreneurial success. These results indicate that entrepreneurial orientation does not only look at business performance that has been seen so far in large and medium-sized companies and in this study looks at MSMEs, which have many limitations in measuring their dimensions because of the difficulty of getting reports on MSMEs. The limitations of research in measuring social capital need to be done qualitatively by involving other dimensions and it is necessary to measure the entrepreneurial orientation of SMEs whether it is appropriate to use 5 dimensions.